Anti-Yo Mediated Paraneoplastic Cerebellar Degeneration Associated with Pseudobulbar Affect in a Patient with Breast Cancer. (9th March 2017) - Martin, Allison N.; Dillon, Patrick M.; Jones, David E.; Brenin, David R.; Lapides, David A.
Abstract : Paraneoplastic cerebellar degeneration (PCD) is a rare anti-Yo mediated paraneoplastic syndromes rarely that is infrequently associated with breast cancer. We present a case of a 52-year-old female presenting with diplopia, gait instability, dysarthria, dysphagia, nystagmus, and, most notably, new onset paroxysmal episodes of uncontrollable crying concerning for pseudobulbar affect (PBA). Serologic testing showed anti-Yo antibodies. The patient was found to have stage IIIA breast cancer as the inciting cause of the paraneoplastic syndrome. The patient was treated with neoadjuvant chemotherapy, modified radical mastectomy, adjuvant Herceptin, and pertuzumab. She was given IVIG for paraneoplastic syndrome, antidepressants, and dextromethorphan-quinidine (Nuedexta), the first FDA-approved therapy for PBA. With multimodality therapy, she demonstrated significant improvement in neurologic and mood symptoms associated with PCD and PBA.